Glucagon‐like peptide‐1 receptor is expressed in human and rodent testis. (11th August 2020) - Caltabiano, Rosario; Condorelli, Daniele; Panza, Salvatore; Boitani, Carla; Musso, Nicolò; Ježek, Davor; Memeo, Lorenzo; Colarossi, Lorenzo; Rago, Vittoria; Mularoni, Valentina; Spadola, Saveria; Castiglione, Roberto; et al.
Abstract: Background: The incretin hormone glucagon‐like peptide‐l (GLP‐1) is an important regulator of post‐prandial insulin secretion, acting through a G protein‐coupled cell surface receptor (GLP‐1R). In addition to its expression in pancreatic β‐cells, several studies suggested that GLP‐1R is located in extra‐pancreatic tissues. Objectives: In this study, we examined for the first time the testicular distribution of the GLP‐1R, both in normal human and neoplastic testicular tissues as well as in rodent testis and rodent testicular cell lines. Methods and Methods: The GLP‐1R distribution in testicular section has been evaluated by immunohistochemistry, the specificity of IHC was validated by demonstrating a positive staining for GLP‐1RmRNA by RISH technology. While GLP‐1R expression in terms of protein was detected by western blot analysis, Moreover, mRNA levels were determined in human testis, in rodent Leydig, and Sertoli cell lines. Results: Using immunohistochemistrya specific staining for GLP‐1R was detected in Leydig cells. The specificity of IHC was validated by demonstrating a positive staining for GLP‐1RmRNA only in these cell types. Species differences in the GLP‐1R expression between humans and rodents were observed. Interestingly, a decreased expression of the receptor in rodent tumor Leydig cell line and an absence in human Leydig tumor samples was detected. Discussion: It may be hypothesized that GLP‐1R acts like an oncosuppressor in Leydig tumors. A role in regulation of hormone secretion by GLP‐1 has been shown in other endocrine cells, therefore we hypothesized that GLP‐1R is able to modulate somehow the Leydig cell function. Conclusion: In our findings, a careful evaluation of human testicular tissues and rodent testis revealed Leydig cells as a potential target for GLP‐1. Collectively, an effect of GLP‐1R in Leydig cell function may be presumed although future studies are needed to ascertain the GLP‐1R's role both in normal and tumor Leydig cells.